The O K−2V spectrum of CO: the influence of the second core-hole. Issue 18 (28th April 2021) - Koulentianos, D.; Carniato, S.; Püttner, R.; Martins, J. B.; Travnikova, O.; Marchenko, T.; Journel, L.; Guillemin, R.; Ismail, I.; Céolin, D.; Piancastelli, M. N.; Feifel, R.; et al.
Abstract : A K −2 V photoelectron spectrum of the CO molecule, showing several core-ionized core-excited states, has been recorded and the different spectral features have been interpreted in terms of their direct or conjugate nature. Abstract : Using synchrotron radiation in the tender X-ray regime, a photoelectron spectrum showing the formation of single site double-core-hole pre-edge states, involving the K shell of the O atom in CO, has been recorded by means of high-resolution electron spectroscopy. The experimentally observed structures have been simulated, interpreted and assigned, employing state-of-the-art ab initio quantum chemical calculations, on the basis of a theoretical model, accounting for their so-called direct or conjugate character. Features appearing above the double ionization threshold have been reproduced by taking into account the strong mixing between multi-excited and continuum states. The shift of the σ* resonance below the double ionization threshold, in combination with the non-negligible contributions of multi-excited configurations in the final states reached, gives rise to a series of avoided crossings between the different potential energy curves.